Effect of tumor necrosis factor inhibitors on interstitial lung disease in rheumatoid arthritis: angel or demon? - Huang Y; Lin W; Chen Z; Wang Y; Huang Y; Tu S (Dove Medical Press, 2019)
Ying Huang, Weiji Lin, Zhe Chen, Yu Wang, Yao Huang, Shenghao TuInstitute of Integrated Traditional Chinese and Western Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaObjectives: This study evaluated the correlation between tumor necrosis factor alpha inhibitor (TNF-I) and interstitial lung disease (ILD) in rheumatoid arthritis (RA). We aimed to raise awareness and consummate therapy by summarizing the characteristics of the adverse events of ILD.Methods: A comprehensive search of the PubMed, Embase, Ovid, Cochrane, China National Knowledge Infrastructure, and Wanfang databases was performed from inception to November 2018. Statistical analysis of demographic characteristics, clinical features, and relative risks was performed using Microsoft Excel 2007 and SPSS version 20.0.Results: A total of 7 eligible articles and another 28 case reports were enrolled. The 7 cohort studies demonstrated the tendency that ILD cases might not benefit from TNF-I therapy. TNF-I might be associated with ILD adverse events. The case reports further confirmed these findings, as most (87.5%) of the cases showed that TNF-1 was harmful to patients with ILD and even resulted in a 35% mortality rate. Further investigation revealed that ILD adverse events tended to appear in female patients with a long RA history (p<0.05). The subgroup analysis suggested that early detection and precise treatment are key factors in determining survival or death when an ILD adverse event occurs. A large proportion of ILD adverse events (48.6%) appeared at 2.38±1.03 weeks after the infusion of infliximab.Conclusion: A fresh look at the evidence highlights that TNF-I might be associated with ILD adverse events in RA, which can induce more severe pulmonary symptoms and even result in death. Therefore, more attention should be paid to effective prevention, early diagnosis, and precise management. Notably, further prospective cohort studies are warranted to better interpret the association or causality between TNF-I and ILD.Keywords: interstitial lung disease, rheumatoid arthritis, tumor necrosis factor inhibitors, adverse effects